2009
DOI: 10.1111/j.1463-1318.2009.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic excision of rectovaginal endometriosis: report of a prospective study and review of the literature

Abstract: Laparoscopic resection of rectovaginal endometriosis may be associated with a higher incidence of complications than resections performed for other diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
3
46
0
1
Order By: Relevance
“…This was also demonstrated in the study of Maytham et al [6] in operations for colorectal endometriosis, which showed a much greater difference with a median age of 33 years in the endometriosis group and 72 years in the control group. However, the lower age of patients compared to controls in our material probably would not influence the result because both groups were mostly premenopausal women.…”
Section: Stage Of Endometriosis (N = 200)supporting
confidence: 61%
See 2 more Smart Citations
“…This was also demonstrated in the study of Maytham et al [6] in operations for colorectal endometriosis, which showed a much greater difference with a median age of 33 years in the endometriosis group and 72 years in the control group. However, the lower age of patients compared to controls in our material probably would not influence the result because both groups were mostly premenopausal women.…”
Section: Stage Of Endometriosis (N = 200)supporting
confidence: 61%
“…Maytham and co-workers [6] also presented median post-operative hospital stay of three days. Both groups were given sick leave for 3-4 weeks on average, indicating a similar postoperative recovery.…”
Section: Stage Of Endometriosis (N = 200)mentioning
confidence: 91%
See 1 more Smart Citation
“…In some of the studies, a radical treatment was assessed [5,13,15,[25][26][27][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], while others assessed a conservative one [57][58][59][60][61][62][63]. There were six nonrandomized papers in which groups of patients with different therapeutic options were compared [30,[35][36][37][38][39]. The follow-up time was not uniform within studies, neither were the criteria used to establish the diagnosis, the extent of the RVE, or the result variables.…”
Section: Resultsmentioning
confidence: 99%
“…All of them are observational studies in which the treatment option was not decided randomly; rather, it was made in terms of clinical criteria or in consensus with the patients [30,[35][36][37][38][39].…”
Section: Comparative Studiesmentioning
confidence: 99%